2016
DOI: 10.1210/en.2016-1472
|View full text |Cite
|
Sign up to set email alerts
|

A Sex-Dependent, Tropic Role for Leptin in the Somatotrope as a Regulator of POU1F1 and POU1F1-Dependent Hormones

Abstract: Pituitary somatotropes perform the key function of coordinating organismic growth and body composition with metabolic signals. However, the mechanism by which they sense and respond to metabolic signals via the adipokine leptin is unknown. The complex interplay between the heterogeneous cell types of the pituitary confounds the identification of somatotrope-specific mechanisms. Somatotropes represent 30%-40% of the anterior pituitary population and are derived from a lineage of cells that are activated by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(46 citation statements)
references
References 55 publications
6
40
0
Order By: Relevance
“…5C ). In fact, further support for a direct positive association between leptin signaling and GH, PRL and Pit-1 expression levels is a recent report demonstrating that adult female, but not male, mice lacking leptin receptor from somatotropes had reduced GH, PRL and Pit-1 protein levels in somatotropes, suggesting a sex-dependent role for leptin in the control of GH, PRL and Pit-1 levels 70 . Remarkably, this study also showed that Pit-1 protein was increased in response to leptin stimulation, which reinforce the idea that leptin might regulate GH levels through stimulation of Pit-1, but also that Pit-1 might be a target of leptin, at least in female mice.…”
Section: Resultsmentioning
confidence: 87%
“…5C ). In fact, further support for a direct positive association between leptin signaling and GH, PRL and Pit-1 expression levels is a recent report demonstrating that adult female, but not male, mice lacking leptin receptor from somatotropes had reduced GH, PRL and Pit-1 protein levels in somatotropes, suggesting a sex-dependent role for leptin in the control of GH, PRL and Pit-1 levels 70 . Remarkably, this study also showed that Pit-1 protein was increased in response to leptin stimulation, which reinforce the idea that leptin might regulate GH levels through stimulation of Pit-1, but also that Pit-1 might be a target of leptin, at least in female mice.…”
Section: Resultsmentioning
confidence: 87%
“…Methods describing our approach to leptin stimulation are detailed in previous studies ( 33 , 52 , 124 , 125 ). Pituitary pieces or cells in 24-h culture are exposed to leptin for 3 h at 37掳C, and then extracts of proteins and mRNA are produced, as described ( 126 ). Methods describing our RT-PCR assays are found in the legend to Figure 3 and in Ref.…”
Section: Hypothesis 1: Cyclic Regulation Of Pituitary Gnrhr Levels Sementioning
confidence: 99%
“…Leptin stimulates an increase in pituitary activin subunit mRNA ( InhBa ) level and does not have an effect on inhibin ( InhBb ) or Gnrhr mRNA levels. (C) In a separate set of experiments, we used fluorescence-activated cell sorting (FACS) to purify gonadotropes from control females bearing Lh-cre and floxed alleles of tdTomato-eGFP as described previously ( 126 ). The Cre-recombinase ablates the tdTomato leaving eGFP to be expressed in membranes of gonadotropes.…”
Section: Hypothesis 1: Cyclic Regulation Of Pituitary Gnrhr Levels Sementioning
confidence: 99%
See 1 more Smart Citation
“…The group later reported more extreme cases of GH deficiency and abdominal obesity in male mice that had selective ablation of exon 1 of OB-Rb in somatotropes [ 45 ]. This excision of OB-Rb exon 1 resulted in the loss of all isoforms of the leptin receptor and uncovered a broader role for somatotropes as metabolic sensors including sex-specific responses to leptin [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%